Effects of knowledge, attitude, practice on food safety compliance among food handlers of school canteens in Kuala Muda, Kedah / Aida Jalani, Hashim Fadzil Ariffin and Sabaianah Bachok - Jalani, Aida; Ariffin, Hashim Fadzil; Bachok, Sabaianah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
The aim of this study is to determine the relationship between knowledge, attitudes, practices and food safety compliance. Questionnaires were distributed to 341 school canteen food handlers from 28 primary and 63 secondary schools respectively in Kuala Muda, Kedah. The responses were analysed using SPSS, Amos version 22.0, Pearson Correlation to analyse the correlation. Structural Equation Modelling (SEM) approach was used to test the research hypotheses and the predictive model. Based on the results, a framework is proposed to integrate knowledge, attitude and practices among the food handlers. The framework provides a more comprehensive understanding of the knowledge, attitude and practices related to this context: (1) correlation between knowledge with food safety compliance (2) a significant relationship between knowledge, attitude and practices with food safety compliance. The findings indicated that knowledge and attitude are significant factors that can improve food handlers' food safety compliance. Surprisingly, the study found insignificant relationship between food handlers practices and food safety compliance. This study concluded that food handlers should improve their knowledge and attitude through continuous awareness and education program in order to avoid issues related to food safety in school canteens.